Clinical Trial of Bawang Dayak Leaves Capsules (Eleutherine americana) in Active Smokers - Wahdaningsih, Sri; Untari, Eka Kartika; Rizkifani, Shoma (Faculty of Pharmacy, Universitas Gadjah Mada, 2024)
Smoking is an unhealthy behavior, particularly for the respiratory system's health due to the free radicals found in cigarette smoke. Eleutherine americana or Bawang Dayak has antioxidant properties which can neutralize the harmful free radicals penetrating the body. Additionally, malondialdehyde (MDA) is one of the stress oxidative biomarkers often applied to identify reactive stress. This study was conducted to determine the effect of Malondialdehyde on active smokers who consumed Bawang Dayak Leaves capsules. This study was a pre and post-test design involving 30 smokers who met the inclusion. The participants consumed 1 capsule containing 400 mg Bawang Dayak leaves extract for 7 days. The subject's blood was taken before and after the consumption of the capsules for MDA examination. The results of this study were that the MDA level between before and after Bawang Dayak capsules consumed statistically significant. Moreover, MDA pre and post-test level respectively were 12.074 nmol/ml and 11.869 nmol/ml. The usage of Bawang Dayak leaves capsules for a week can reduce MDA levels and likely has an antioxidant potential for active smokers.